Edukasi Cuci Tangan Dalam Meningkatkan Perilaku Hidup Bersih Sehat (PHBS) Di TK Al-Munawwarah Pekanbaru: Edukasi Cuci Tangan Dalam Meningkatkan Perilaku Hidup Bersih Sehat (PHBS) Di TK Al-Munawwarah Pekanbaru - Busyra Hanim; Nisa Dewi; Yusdalihafi Rosanti; Nofrya Amanda; Shella Dih Nenanda; Arfaeni Febrian Abdilah Tifah; Dila Safitri; Niken Ayu Kurniawati; Leny Kusuma Sofie Sitompul; Rizka Annisa; Nurul Safika; Irna Silvia; Tiara Tisnawati; Tiara Dwi Pitri; Ayu Wandira Br Ginting (Ruang Ide Publisher, 2026)
Implementing clean and healthy living behaviors from an early age is crucial for preventing diseases such as diarrhea and flu. This educational activity aims to improve the understanding of children at Al-Munawwarah Kindergarten in Pekanbaru about the importance of the six-step handwashing with soap (CTPS). Education was delivered through images, videos, songs, and live demonstrations, followed by evaluation in the form of questions and answers and repeated practice. The results of the activity showed an increase in the children's understanding and skills in washing their hands properly. Interactive and fun education has proven effective in instilling healthy habits in young children.